Sertraline-induced Hemichorea. (18th December 2017) - Gatto, Emilia M.; Aldinio, Victoria; Parisi, Virginia; Persi, Gabriel; Da Prat, Gustavo; Bullrich, Maria Bres; Sanchez, Pilar; Rojas, Galeno
Background: Hemichorea–hemiballism is a syndrome secondary to different etiologies. Drug-induced hemichorea is a rare syndrome related to selective serotonin reuptake inhibitors. To the best of our knowledge, no previous cases of hemichorea associated with sertraline have been reported. Case Report: A 65-year-old female noticed hemichorea 1 week after initiation of sertraline. After extensive investigations, other causes of hemichorea were excluded. Hemichorea remitted after sertraline withdrawal. Discussion: In our patient, temporal association and the negative clinical assessment supported a diagnosis of likely drug-induced involuntary movement. We hypothesized that enhanced serotonergic transmission in the ventral tegmental area or nigrostriatum may be involved in sertraline-induced hemichorea.